Pengaruh Profitabilitas, Total Arus Kas, Likuiditas Terhadap Harga Saham - Simangunsong, Febriyanti; Purwaningsih, Eny (Shofanah Media Berkah, 2024)
Stock prices reflect investors' expectations and have a significant influence on investors' decisions to invest or not to invest. Every investor needs to have knowledge about changes in stock trading. Some key data that investors can use to measure stock price movements include profitability, total cash flow, and liquidity. The relationship between the seller's and the buyer's share prices in the capital market is because the value of shares is always changing. The purpose of this research is to investigate how the relationship between stock price, profitability, total cash flow, liquidity relates to one another. The sample variable for this research is the food and beverage sub-sector entities listed on the IDX from 2018 to 2021. To select these companies using a porposive sampling method, and the criteria used only cover entities that issue financial reports from 2018 to 2021. Multiple regression analysis is used in the methodology This. This study shows that profitability, total cash flow, liquidity affect stock prices. Furthermore, the findings show that share prices are positively influenced by profitability, total cash flow, and liquidity.